GROWTH AND YIELD OF FLUTED PUMPKIN [Telfairia occidentali (Hook F)] AS INFLUENCED BY TILLAGE PRACTICE AND STAKING METHODS IN THE SUDAN SAVANNAH OF NIGERIA - Rufa’i, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
Field trials were conducted to study the influence of tillage practices and staking methods on the growth and yield of fluted pumpkin, during 2018 rainy session at the Teaching and Research Farm, Bayero University, Kano (Latitude 11°58’N and Longitude 8°25'E), and Kano Institute of Horticulture Bagauda, Kano (Latitude 11°33'N and Longitude 8°34'E) both located in the Sudan savanna of Nigeria. The treatments consisted of three (3) tillage practices (zero tillage, conventional tillage, and conservational tillage) and three (3) staking methods (individual, pyramidal, and non-staked), these were factorially combined to give nine (9) treatments and laid out in a split plot design, replicated four (4) times with tillage practices allocated to the main plot while staking methods were placed in sub-plots. Results indicated that tillage practices had distinct effects on many growth parameters (vine length, number of leaves) depending on the location. In some cases, minimum and conservational tillage practices resulted in more leaves at Bagauda and longer vines at 6 WAS (94.5 cm) and at 12 WAS (160.1cm) at BUK, potentially due to improved soil properties across the locations. Staking methods significantly influenced branching only at Bagauda and later in the growth cycle. Similarly, non-staking (4.091) and pyramidal staking (4.225) encouraged more branching compared to individual staking (3.667), likely due to better support and resource allocation. Tillage and staking methods generally did not significantly impact leaf length across locations, suggesting a potential genetic influence on leaf size in the fluted pumpkin variety used. The combination of tillage and staking methods can influence leaf growth, but the optimal combination depends on the growth stage and location. Therefore, conservational tillage with pyramidal staking could be employed by farmers of fluted pumpkin in the study area to enhance growth and yield.